KINERJA SISTEM AGRIBISNIS KOPI PADA KOPERASI PRODUSEN SRIKANDI MAJU BERSAMA KECAMATAN ULU BELU KABUPATEN TANGGAMUS - Misrianti, Nunik; Lestari, Dyah Aring Hepiana; Adawiyah, Rabiatul (Lampung University, 2024)
The purpose of the research is to investigate the performance of coffee agribusiness system at the cooperative namely Produsen Srikandi Maju Bersama. The method used in this study was a case study method, involving 71 coffee farmers members of the cooperative Produsen Srikandi Maju Bersama, five cooperative managements as processor, and three retailers. The samples were selected by snowball sampling method. The data analysis was carried out using the agribusiness index system. The data were collected from May to - July 2022. The results show that subsystem index for the procurement of production, farming, processing, facilities, and supporting services are in good categories. In the meantime, the marketing subsystem’s index for the coffee is categorized as not good. Overall, coffee agribusiness system at the cooperative Produsen Srikandi Maju Bersama is categorized as good with total score of 11,95 (79,68 percent) from a maximum score of 15,00. keywords: agribusiness system performance, coffee, cooperative